Moderasi Konten dalam Perspektif Hukum dan Etika Digital: Menemukan Keseimbangan antara Ketertiban Ruang Digital dan Kebebasan Berekspresi di Indonesia - Gilang Rizki Aji Putra; Sri Ajeng Murni Cahyani Putri (UIN Jakarta, 2025)
Content moderation has become a central governance mechanism for digital platforms, intersecting law, ethics, and business interests. This article examines Indonesia’s content moderation framework and its capacity to balance public order with freedom of expression. Using normative legal research, the study finds that Indonesia applies a government-driven notice-and-takedown model, reinforced by the Content Moderation Compliance System (SAMAN), while platform policies operate under separate standards. The regime raises due process concerns, including vague definitions of illegal content, limited transparency, and weak user remedies. The article concludes that stronger transparency rules, regulatory harmonization, and independent oversight are essential to ensure accountability and rights protection. Keywords: Content Moderation, Notice and Takedown, SAMAN, Due Process, Freedom of Expression.